(3fZeg GdCZGfj aj YTQI GdENhGfs - (3GdMSjfj, GdOTJcj, Ydj NGfs ((3SjO eMeOs)
(3ChdgG (B:s
(3jbhd QGLj GdUeO(B***(3Ydj Hf CMeO , MeOG def gOGfj(B***(3HGdfWb hGdHjGfs
(3BNQgG (B:s
(3eG fGM WjQ hTOG(B***(3hdGM aLQ hHOGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdPQjYI(B:(3L(B24(3,U(B228(3,Qbe(B1223s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
Keywords: (3GdJUha hGdBOGH GdTQYjIs